STRATEGI KOMUNIKASI PEMASARAN PEMERINTAH DESA WISATA BANJAREJO DALAM PEMANFAATAN INSTAGRAM @DESAWISATABANJAREJO - Rizki Ayun Agidiya Sari; Nunik Hariyanti (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
A marketing communication strategy is an activity carried out to market its products to be known by many people. A marketing mix is ​​a tool for a company to achieve the right target market. Marketing communication is essential to do to encourage the success of marketing activities. Banjarejo Tourism Village applies this to determine the development and improvement of tourism in Banjarejo Tourism Village. This research is located in Banjarejo Village, Gabus District, Grobogan Regency, Central Java. This study aimed to determine the marketing communication strategy used by Banjarejo Tourism Village via Instagram@desawisatabanjarejo. The results of this study indicate that the marketing communication strategy implemented by the Banjarejo Village government by utilizing social media Instagram uses the Kotler 7P marketing concept, including product, price, place, promotion, people, process, and physical evidence. Based on the marketing mix, five marketing strategies have been running well and maximally. Meanwhile, the two marketing mixes that are less than optimal are people and promotion. In this case, less than optimal does not mean in vain, only less effective in carrying it out. Behind that, in terms of place, it is very supportive of marketing in the Banjarejo Tourism Village.